Influence of Saccharomyces cerevisiae and Lachancea thermotolerans co-inoculation on volatile profile in fermentations of a must with a high sugar content. (15th March 2019) - Morales, M.L.; Fierro-Risco, J.; Ríos-Reina, R.; Ubeda, C.; Paneque, P.
Highlights: Sun-dried grape musts were fermented by co-inoculation of indigenous strains. Lachancea thermotolerans strain tolerates and ferments high-sugar must. Multivariate Curve Resolution is a suitable tool for wine volatile profile processing. Wines volatile profile depended on the ratio of each yeast strain in the inoculum. Co-inoculated fermentations seem to increase aromatic complexity in wines. Abstract: The aim of this work was to evaluate how the use of mixed cultures of Saccharomyces cerevisiae and Lachancea thermotolerans indigenous yeast strains influences the volatile composition of wine. Multivariate curve resolution (MCR) method has been applied to data analysis. Five fermentation trials were carried out: three co-inoculated with L. thermotolerans:S. cerevisiae, at the ratio of 50:1, 20:1 and 5:1 respectively, and two with a pure culture of each strain. A must from sun-dried Pedro Ximénez grapes was employed. Volatile composition was determined by dual sequential stir bar sorptive extraction, followed by GC–MS analysis. MCR provided 171 peaks. Results in co-inoculation fermentations revealed that the majority compounds obtained in each case followed the same trend as that observed for the pure culture of the strain that was present in a higher proportion. Finally, 50:1 and 20:1 seemed to be the best proportions to obtain a wine with a quality volatile profile.